Trust as the cement in the employment relationship? The role of trust in different workplace employment relations regimes - Brandl, Bernd (Journal of Organizational Effectiveness: People and Performance, 2025)
This paper addresses the puzzle of why the same workplace employment relations regimes can lead to different performances and why different regimes can produce the same performance. It is argued that the incidence of mutual, and not necessarily unilateral, trust between the employee representation and the management accounts for these differences, as mutual trust fosters information sharing and helps to strike deals that are mutually beneficial. Against the background that the institutional and organisational characteristics of some workplace employment relations regimes also constitutes information sharing and joint decision making, we further argue that mutual trust is a functional equivalent.
EPrint Processing Status: Full text deposited in DRO